Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids - Makarkin, Vladimir N. (Zootaxa, 2018)
Grammapsychops lebedevi Martynova, 1954 from the Late Cretaceous (Cenomanian) of Siberia is re-described based on the holotype. The species is represented by a hind wing as its CuA is definitely concave, although the costal space is strongly dilated. This genus together with three other Cretaceous genera (i.e., Embaneura G. Zalessky, 1953, Kagapsychops Fujiyama, 1978, and probably Pulchroptilonia Martins-Neto, 1997) form the Grammapsychops genus-group. The hind wing of Grammapsychops may theoretically be associated with forewings of Kagapsychops or other closely related genera with similar forewing venation. The Late Cretaceous psychopsoids are critically reviewed. All known psychopsoid taxa from this interval are considered as belonging to Psychopsidae.